Natural tricks to save time in bean breeding - Debouck, Daniel G. (2022)
CGIAR meta data: Saving agrobiodiversity, Reducing hunger and malnutrition; reach: global excluding (sub-) artic regions. Palmira, 24 May 2022 [virtual]. Alliance of Bioversity International and CIAT